Improving learning skills of college student through mastery content service in technique counseling courses - Folastri, Sisca; Rangka, Itsar Bolo; Rahmaniah, Ayu (COUNS-EDU: The International Journal of Counseling and Education, 2018)
Counseling skills is one component of the expertise that must be possessed by prospective counselors who study in university. It requires adequate student learning skills to succeed in mastering counseling skills. This study aimed to improve students' learning skills through content services over the course of counseling techniques. The study involved 61 students used the one group pretest-posttest design. The result from the research showed that there is influenced of delivering masterycontent service to student's learning skill in a course of counseling technique.